Mosques and mosques in Egypt and the Levant in the Ayyubid era: 567 AH-648 AH / 1172 AD-1250 AD - Merin, Forat; Al-Rawi, Qusay (Al-Adab Journal, 2024)
This research aims to highlight mosques and mosques in the Ayyubi era in Egypt and the Levant and the interest of the Ayubans in them for their religious importance as places of worship and for their political importance in advocating jihad as well "This research examined the efforts of the Iowans to build a number of mosques and mosques in belief in their importance, as well as the renovation and reconstruction of a number of them built during the Fatimid State.The research attempts to highlight the mosques built by Sultans, kings and men of the Ayubian State in Egypt and the Levant as Asaduddin Shirku mosque in Aleppo and Nimdin Ayyub mosque in Zahir Bab al-Nasser, one of the gates of Cairo, the new mosque in Damascus and the mosque in Damascus. Historical sources indicate that the mosques built in the Ayyubi era were very little, and that the Eyubans may have replaced the construction of mosques with the establishment of schools, which are religious educational institutions that combine the mosque’s religious function with that of the school. The research also showed mosques and mosques renovated in the Ayyubi era, built in the Fatmi era as the mosque of Amr bin al-Az (the antique mosque) in Fattat, the Amwi mosque in Damascus and the mosque of Ibn Toulon in Cairo.